Popular Sovereignty and the Crisis of German Constitutional Law : The Theory and Practice of Weimar Constitutionalism - Caldwell, Peter C. (Book collections on Project MUSE., 1997)
Popular Sovereignty and the Crisis of German Constitutional Law is a historical analysis of competing doctrines of constitutional law during the Weimar Republic. It chronicles the creation of a new constitutional jurisprudence both adequate to the needs of a modern welfare state and based on the principle of popular sovereignty. Peter C. Caldwell explores the legal nature of democracy as debated by Weimar's political theorists and constitutional lawyers. Laying the groundwork for questions about constitutional law in today's Federal Republic, this book draws clear and insightful distinctions between strands of positivist and anti-positivist legal thought, and examines their implications for legal and political theory.